Student Pleasure Attitude and Interest in Spending Time Learning Science Against Student Cognitive Learning Outcomes: Sikap Senang Siswa Dan Minat Meluangkan Waktu Belajar IPA Terhadap Hasil Belajar Kognitif Siswa - Nur Fadilah; Nur Efendi (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to analyze the relationship between students 'attitudes in science and cognitive learning outcomes based on 2 indicators that is enjoyment of science lessons and leisure interest in science. This type of quantitative research with a survey method. The instrument used was a questionnaire which was tested through the google form application. The results showed that enjoyment of science lessons was categorized as good with a percentage of 54%. Leisure interest in science is categorized quite good with a percentage of 42%. Based on the correlation analysis of enjoyment of science lessons and learning outcomes, it shows a positive correlation with a correlation level of 0.607 which is classified as a strong correlation. The correlation of leisure interest in science and learning outcomes shows a positive correlation with a correlation level of 0.499 which is classified as moderate correlation. Meanwhile, the correlation between the two indicators shows a positive correlation with the level of correlation of 0.776 which is classified as a strong correlation. It can be concluded that the students' attitudes towards science at MTs Muhammadiyah 1 Taman based on these indicators are classified as having positive attitudes and are categorized as good.